Utilizing YouTube Videos to Improve Speaking Skills in Seventh-Grade Students at MTsN 2 Kota Bengkulu - Syaputra, Abdul Yongky; Nurwita, Syisva (PPSDP International Journal of Education, 2024)
This study aimed to explore how YouTube digital videos could enhance students’ speaking skills and to identify the factors that influenced these improvements. Conducted as Classroom Action Research, the study involved 36 seventh-grade students at MTsN 02 Kota Bengkulu. The research employed a mixed-methods approach, gathering both quantitative data through speaking tests and qualitative data through observations, field notes, and interviews. The results revealed that key factors driving this improvement included increased student motivation and active participation in the learning process. Students reported feeling more confident in their speaking abilities, and the authentic language input provided by YouTube videos helped them improve their pronunciation, vocabulary, and fluency. The novelty of this study lay in applying YouTube as a pedagogical tool within an Indonesian junior high school context, specifically focusing on its impact on speaking skills. Furthermore, the study highlighted the importance of combining digital media with interactive classroom activities to create a more engaging and effective learning environment. This research contributed to the growing body of literature on digital media in education by offering practical insights into how YouTube videos could be successfully integrated into language teaching to foster speaking skill development among younger learners. The findings suggested that YouTube digital videos served as an effective medium for improving language proficiency, particularly in EFL (English as a Foreign Language) contexts, where authentic language exposure was often limited. Moreover, the study emphasized the crucial role of motivation and student engagement, offering valuable strategies for educators to implement in their classrooms to enhance student learning outcomes.